David Copperfield - Dickens, Charles, 1812-1870 (Oxford University Press, 1999)
Ì have in my heart of hearts a favourite child. And his name is DAVID COPPERFIELD, ' wrote Dickens of what is the most personal, certainly one of the most popular, of all his novels. Dickens wrote the book after the completion of a fragment of autobiography recalling his employment as a child in a London warehouse, and in the first-person narrative, a new departure for him, realized marvellously the workings of memory. The embodiment of his boyhood experience in the novel involved a c̀omplicated interweaving of truth and fiction', at its most subtle in the portrait of his father as Mr Micawber.
Keywords: England -- Social life and customs -- 19th century -- Fiction.; Young men -- England -- Fiction.; Angleterre -- Mœurs et coutumes -- 19e siècle -- Romans, nouvelles, etc.; Jeunes hommes -- Angleterre -- Romans, nouvelles, etc.; FICTION -- Coming of Age.; Manners and customs; Young men; England; 1800-1899; Bildungsromans; Autobiographical fiction; Fiction; Autobiographical fiction.; Bildungsromans.